Smart Car Design Using Arduino Uno Based Speech Recognition Application - Febri Wiranata; Fitri Artika; Maya Selviana; Suriano; David J.M. Sembiring; Eriansyah Saputra Hasibuan (Karya Techno Solusindo, 2025)
Designing a smart car using a speech recognition application based on Arduino Uno is an effort to improve vehicle control by utilizing speech recognition technology. Through the implementation of a speech recognition application, drivers can easily control various aspects of the vehicle such as the drive system, brake system, or navigation system, just by using their voice. In the design process, there are several areas that need to be considered, including needs analysis, speech recognition method selection, integration with existing vehicle systems, and intuitive user interface design. The final result of designing a smart car using an Arduino Uno-based speech recognition application is a vehicle system that allows the driver to control the vehicle using voice commands. This design provides a more intuitive driver experience, improves driving safety, and strengthens integration between voice technology and vehicle systems.